Youth Mental Health Initiative : Evaluation Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Your Mental Health Initiative Impact Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2022)
Within the Youth Mental Health Initiative’s (YMHI) second year, CHSSN supported 27 community organizations with over 373 partnerships across 12 regions of Quebec including three provincial organizations, with the central goal of improving the access of mental health services and resources to Quebec’s English-speaking youth between the ages of 15-29. Each organization has worked to identify gaps in youth mental health services; engage youth in program design; partner with local schools, public health services and other community organizations; adapt, translate, and produce resources; and offer activities and programs for young people to help fill some of the gaps. Through a community of practice and individualized support, CHSSN helped community organizations to build their knowledge, network with each other and problemsolve on program implementation.

Y4Y Quebec and ECO-02 Invite Youth to Attend a Bilingual Panel Discussion on Locals’ Opinion of Law 96 - Youth for Youth Québec (Y4Y Québec) (2022)

Working Together Pays Dividends for Official Language Minority Communities! - Quebec English-language Production Council; Quebec Community Groups Network (QCGN); English Language Arts Network (ELAN); Alliance nationale de l'industrie musicale; Alliance des producteurs francophones du Canada (APFC); Fédération culturelle canadienne-française (FCCF) (2022)

Working Together for a More Vital Community : The 2022-2027 Community Developmet Plan for English-speaking Quebec - Community Vitality Roundtables (Quebec Community Groups Network (QCGN), 2022)
The community sector serving English-speaking Quebec cultivates a sustained, ongoing capacity to collect, analyze, and share information (qualitative and quantitative) necessary to more deeply understand our community.

What the Community School Approach Brings to Quebec's English School Sector: Connections, Connections, Connections - Horrocks, Debbie; Loomer, Benjamin; Lamarre, Patricia (Lunch & Learn, 2022)

Videoconferencing with Older Adults : Best Practices for Psychosocial Group Interventions - Aubin, Ginette; Larivière, Nadine; Marcoux, Lyson; Couture, Mélanie; Charbonneau, Hélène (Community Health and Social Services Network, 2022)
This document presents an overview of the recommended practices for videoconferencing with older adults in the framework of psychosocial group interventions.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Update on Strategic Plan 2022 -2026 / Point d'information sur le plan stratégique - Garcia, Patricia (2022)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2022)

The Partnership Approach : Celebrating Resiliency Conference - Pocock, Joanne (2022)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

The Advisor - Assistance and Referral Centre (ARC) (2022)

The Advisor - Assistance and Referral Centre (ARC) (2022)

The Advisor - Assistance and Referral Centre (ARC) (2022)

The Advisor - Assistance and Referral Centre (ARC) (2022)

The Advisor - Assistance and Referral Centre (ARC) (2022)

Strategic Restructuring Plan : The Road Ahead - Maurice, Cornella; Buffitt, Kimberly; Fequet, Roderick; Keats, Shannon; Griffin, Priscilla; Maynard, Hugh; Geukjian, Nadia (Coasters Association, 2022)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

September 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Seniors Action Quebec Announces Change to Board of Directors - Seniors Action Quebec (SAQ) (2022)

Senior Safety Plan : Raising Awarness of Elder Abuse on the Lower North Shore - Maurice, Jenna; Kippen, Kayla (Coasters Association, 2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Semaji - Black Community Resource Centre (BCRC) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

Resolution 2022-08 : Quebec English CEGEP Admissions Policy - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-07 : Quebec English CEGEP Curricula - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-06 : Immigrating Ukrainian Children - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-05 : The Offering of Bilingual Services by Student Ombudsmen - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-04 : Request to Be Included in Future Consultations as a Partner in Education - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-03 : A Call to Suspend and Amend Law 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-01 : Objection to the Definition of “Historic” Anglophones and the Consequent Restrictions to Eligibility for Services in English - Quebec Federation of Home and School Associations (QFHSA) (2022)

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

Récits d’un petit “shtetl” : histoire de la communauté juive de Drummondville - Miller, Julie (2022)

RAWQ Appoints Paul Tonkin as Executive Director - Ayers, Arthur (2022)

Rapport du Comité de résidents du Jeffery Hale : Année 2021-2022 - Cloutier, Robert (Jeffery Hale - Saint Brigid's (JHSB), 2022)
Au cours de 2021-2022, le Comité de résidents du Jeffery Hale a tenu dix séances de travail via Zoom compte tenu des exigences sanitaires Covid-19. Ce mode de fonctionnement a permis aux membres du Comité de maintenir le lien d’appartenance et de réaliser des projets d’amélioration de la qualité de vie des résidents et leurs proches.

Rapport d'impact 2021-2022 - 4Korners (2022)

Rapport Annuel du 1er avril 2021 au 31 mars 2022 - Quebec English-speaking Communities Research Network (QUESCREN) (2022)

Rapport annuel : 2021-2022 - NDG Community Council (NDGCC) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News Bulletin : Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QDF's Membership & Community Summit Schedule - Quebec Drama Federation (QDF) (2022)

QCGN Congratulates Eric Girard, New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Press Release : Seniors Action Quebec Announces Appointment of New Executive Director - Seniors Action Quebec (SAQ) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

Operating Rules - McGill Community For Lifelong Learning (MCLL) (2022)

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

November 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Nos pionniers locaux! : Un balado sur la contribution et la collaboration entre les francophones et les anglophones à la société québécoise en Outaouais d’hier à aujourd’hui. - Nivischiuk, Jeanne (2022)

Newsletter : October - December 2022: Volume 26 - Jamaica Association of Montreal (JAM) (2022)

Newsletter : July - September 2022 : Volume 25 - Jamaica Association of Montreal (JAM) (2022)

Newsletter: August 2022 : Independence Special Edition : Volume 25.1 - Jamaica Association of Montreal (JAM) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Monteregie West Healthcare Information Booklet for English Speakers - Montérégie West Community Network (MWCN) (2022)

Minutes of the Annual General Meeting of “Agape” Inc. - AGAPE (2022)

May 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

March 2022 : Newsletter - Coasters Association (2022)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

March 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Legislative Update, Bill C-13 An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Community Groups Network (QCGN) (2022)

Le réseau des écoles communautaires du Québec - Leading English Education and Resource Network (LEARN) (2022)
Keywords: Official Language Minority Community (OLMC)

Le QCGN félicite Éric Girard, nouveau ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le QCGN demande la nomination d’un ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)

Latest Y4Y Quebec Research Outlines What Makes Quebec’s English-Speaking Youth (ESY) a Unique Set of Civic Actors: Quebec’s ESY Speak on the Driving Forces Behind their Civic Engagement. - Winrow, Adrienne (2022)

L’initiative sur la jeunesse et la santé mentale – rapport d'impact 2022-2023 - Community Health and Social Services Network (CHSSN) (2022)
Au cours de la deuxième année de l'initiative sur la jeunesse et la santé mentale (surnommée « YMHI »), le CHSSN a soutenu 27 organismes communautaires avec plus de 373 partenariats dans 12 régions du Québec, y compris trois organismes provinciaux, dans le but principal d'améliorer l'accès aux services et aux ressources en matière de santé mentale pour les jeunes d’expression anglaise du Québec âgés de 15 à 29 ans. Chaque organisation s'est efforcée d'identifier les lacunes dans les services de santé mentale pour les jeunes, d'impliquer ces derniers dans la conception des programmes, d'établir des partenariats avec les écoles locales, les services de santé publique et d'autres organisations communautaires, d'adapter, de traduire et de produire des ressources, et d'offrir des activités et des programmes pour les jeunes afin de contribuer à combler certaines lacunes. Grâce à une communauté de pratique et à un soutien individualisé, le CHSSN aide les organismes communautaires à renforcer leurs connaissances, à travailler en réseau et à résoudre les problèmes liés à la mise en œuvre de leur programme.

June 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

July & August 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

July 2022 : Newsletter - Coasters Association (2022)

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report: 2021-2022] - Robertson, Mary (Jeffery Hale - Saint Brigids (JHSB), 2022)
The Jeffery Hale-St. Brigid’s Users’ Committee met ten times from April 2021 to March, 2022 plus at the Annual Meeting on June 7, 2021. There were no in-person meetings held because of the Public Health constraints imposed by the COVID 19 worldwide pandemic so all meetings were held through Zoom. Some of the main challenges this public health situation has presented to the Committee have been the difficulty of meaningfully supporting staff in both residences, limited in- person access to Residents and their families, recruiting new members, and the complications in planning and implementing programmes.

January 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Jamaica Association of Montreal Newsletter : Jan - Mar 2022 : Vol. 23 - Jamaica Association of Montreal (JAM) (2022)

Jamaica Association of Montreal Newsletter : Apr. - Jun. 2022 : Vol. 24 - Jamaica Association of Montreal (JAM) (2022)

Jamaica Association Election 2022 : Saturday, December 10, 2022 : 7pm About the Candidates - Jamaica Association of Montreal (JAM) (2022)

Initiative sur la jeunesse et la santé mentale : Rapport d’évaluation - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Impact Report 2021-2022 - 4Korners (2022)

Impact Report : 2021-2022 - Megantic English-speaking Community Development Corporation (MCDC) (2022)

High School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

Follow-up Report - Maurice, Cornella (Coasters Association, 2022)

February 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Fall 2022 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2022)

English : an Asset! - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

Elementary School Workshop Catalogue : 2022-2023 School Year - English Language Arts Network (ELAN); Leading English Education and Resource Network (LEARN) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Directory of Lawyers, Accountants, Notaries, & Real Estate : 2nd Edition - Cyr, Cathy; Wright, Tonya; Dade, Samantha (2022)

December 2022 & January 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

December 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Concert de Noël : Chants et souvenirs de Noël - Centre for Access to Services in English (CASE) (2022)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2022)

Communiqué : Y4Y Québec et ECO-02 convient les jeunes à une soirée de discussion visant à émettre leur opinion sur la loi 96 - Youth for Youth Québec (Y4Y Québec) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Comité des usagers : Rapport annuel 2021-22 - Robertson, Mary (Jeffery Hale - Saint Brigids (JHSB), 2022)
Le Comité des usagers Jeffery-Hale-Saint-Brigid’s s’est réuni à dix (10) reprises entre le mois d’avril 2021 et mars 2022, avec une réunion générale annuelle le 7 juin 2021, par la plateforme ZOOM. Il n’y a pas eu de séances en présentiel, compte tenu de la pandémie COVID-19. Parmi les principaux défis pour le comité, en raison de cette situation d’urgence sanitaire, il y avait la difficulté à apporter un soutien significatif au personnel dans les deux établissements, l’accès restreint aux résidents et leurs familles, la difficulté de recruter de nouveaux membres pour les comités ainsi que de planifier et mettre en œuvre des programmes.

Coasters Staff Contact List - Coasters Association (2022)

Coasters 27th General Meeting & 33rd Anniversary Program - Coasters Association (2022)

Coasters 27th General Meeting & 33rd Anniversary - Coasters Association (2022)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2022)

[Centres scolaires communautaires : Fiche d'information] - Leading English Education and Resource Network (LEARN) (2022)

[Centres scolaires communautaires : Fiche d'information] - Leading English Education and Resource Network (LEARN) (2022)

Booklet for Young Workers : Everything you Need to Know for your First Job - Montérégie West Community Network (MWCN); Educaloi (2022)

Board of Directors : 2022-2024 - Coasters Association (2022)

Arts-Based Performances, Perspectives, and Approaches in Research and Pedagogy - Leading English Education and Resource Network (LEARN) (2022)

April 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

April 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Annual Report : April 1, 2021 to March 31, 2022 - Quebec English-speaking Communities Research Network (QUESCREN) (2022)

Annual Report 2021-22 - Committee for Anglophone Social Action (CASA) (2022)

Annual Report : 2021-2022 - Community Health and Social Services Network (CHSSN) (2022)

Annual Report 2021-2022 - Montérégie West Community Network (MWCN) (2022)

Annual Report : 2021-2022 - NDG Community Council (NDGCC) (2022)

Annual Report 2021-2022 - Youth for Youth Québec (Y4Y Québec) (2022)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

Annual Report - Vision Gaspé-Percé Now (2022)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2022)

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Aller au-delà des solitudes : Contributions, pratiques linguistiques et identités des Québécois anglophones - O'Donnell, Lorraine; Donovan, Patrick (2022)

AGM Minutes : March 22, 2022 - Griffin, Priscilla (Coasters Association, 2022)

Activity Report : A Year In Review 2021-22 - Literacy Quebec (LQ) (2022)

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

4Korners Activities - 4 Korners Family Resource Center (2022)

41st Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2022)

2021-2022 Annual Report : Saint Brigid's Home Residents' Committee - King, Kerry-Anne (Jeffery Hale - Saint Brigid's (JHSB), 2022)

2021-2022 : Annual Report / Rapport annuel - Seniors Action Quebec (SAQ) (2022)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)